Red Blood Cell Transfusion Independence Following the Initiation of Iron Chelation Therapy in Myelodysplastic Syndrome - Maha A. Badawi; Linda M. Vickars; Jocelyn M. Chase; Heather A. Leitch (Advances in Hematology)
Iron chelation therapy is often used to treat iron overload in patients requiring transfusion of red blood cells (RBC). A 76-year-old man with MDS type refractory cytopenia with multilineage dysplasia, intermediate-1 IPSS risk, was referred when he became transfusion dependent. He declined infusional chelation but subsequently accepted oral therapy. Following the initiation of chelation, RBC transfusion requirement ceased and he remained transfusion independent over 40 months later. Over the same time course, ferritin levels decreased but did not normalize. There have been eighteen other MDS patients reported showing improvement in hemoglobin level with iron chelation; nine became transfusion independent, nine had decreased transfusion requirements, and some showed improved trilineage myelopoiesis. The clinical features of these patients are summarized and possible mechanisms for such an effect of iron chelation on cytopenias are discussed.